2019
DOI: 10.25165/j.ijabe.20191204.4287
|View full text |Cite
|
Sign up to set email alerts
|

Development of agricultural bionic four-legged robot: Effect of head movement adjustment on the stability of goats

Abstract: The four-legged bionic robot for agriculture has been one of the hotspots in the field of robotics. The farmland environment is complex, and the balance requirement of quadruped bionic robot is higher. However, head adjustment is a key factor affecting the balance of quadruped animals. Based on this, this study takes the four-legged animal goat as an example to investigate the effect of goat head movement adjustment on the balance of goat. In this study, the head and neck of goats were simplified to a two-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The previous study by the research group found that goats had better rear hoof adhesion under the condition of uphill movement [ 15 , 16 ]. Therefore, the left rear hoof of a 3-month-old male domestic Boer goat was selected as the research object in this paper.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study by the research group found that goats had better rear hoof adhesion under the condition of uphill movement [ 15 , 16 ]. Therefore, the left rear hoof of a 3-month-old male domestic Boer goat was selected as the research object in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers have found that the hoof ends of goats’ limbs have evolved into irregular shapes that can adapt to different ground conditions, and the hoof end structure changes dynamically when interacting with the ground conditions, and they can move on complex ground conditions such as uneven or soft ground conditions [ 15 , 16 ], showing strong adhesion and passing ability, which can provide bionic inspiration for the design of bionic track shoe patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Bionics design uses biological structure and functional principles to develop relevant equipment [148] , which is expected to provide an important opportunity for the development of agricultural robot technology. The joint and configuration design of six-legged agricultural robots has been carried out by Zhang [149] , Rong [150] and Zhang [151] .…”
Section: Bionic Design Technology For Agricultural Robotsmentioning
confidence: 99%
“…Compared with other tetrapods, goats have smaller bodies, solid and powerful limb bones, and agile and light gait, and as well as this, they can adapt to different rugged terrain and road surface changes, showing strong movement stability [ 15 , 16 , 17 ]. In order to explore the structural characteristics of the goat spine, Van Engelen et al [ 18 ] used a structural vibration test method to study the mechanical properties of goat spine motion segments.…”
Section: Introductionmentioning
confidence: 99%